Nanopore Sequencing Technology: Working Principle, Key Issues and Applications - Xiao, Longyu (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Achieving rapid and accurate DNA sequencing is of great clinical value for the detection of many infectious diseases. By determining the nucleic acid sequence of the sample, DNA sequencing can achieve rapid and accurate identification of infectious diseases. Moreover, this method has high detection flux and short time consumption, and it is increasingly used in clinical diagnosis and epidemic prevention. This Review discusses recent advancements in nanopore fabrication and sensing strategies. In this work, the speed control factors of DNA translocation across nanopores are discussed. The identification of multiple types of DNA modification are outlined. Besides, strategy for the multiplexed detection of analytes is also discussed. This technology can achieve sequencing of DNA, RNA, and proteins. It is considered to exhibit high sensitivity, selectivity and efficiency. This work will help people gain a deeper understanding of DNA sequencing technology using nanopores. This work will also promote the development of early diagnostic techniques in the future.